Microsoft Exchange Server 2013 databases, services, & management : pocket consultant - Stanek, William R. (Pocket consultant., 2013)
Portable and precise, this pocket-sized guide delivers ready answers for managing databases and services in Exchange Server 2013. Zero in on core tasks through quick-reference tables, instructions, and lists. You'll get the focused information you need to save time and get the job done-whether at your desk or in the field. Coverage includes: Managing databases and availability groups Core database administration Compliance and role-based access controls Managing mail flow Working with client access servers Managing mobile users Maintenance, monitoring, and queuing Backups and restorations.